2012
DOI: 10.1002/chem.201200523
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Phosphoric Acid‐Catalyzed Enantioselective Three‐Component Povarov Reaction Using Cyclic Enethioureas as Dienophiles: Stereocontrolled Access to Enantioenriched Hexahydropyrroloquinolines

Abstract: Three become one: Phosphoric acid-catalyzed enantioselective three-component Povarov reactions of aldehydes, anilines, and endocyclic enethioureas have been developed (see scheme). This process afforded hexahydropyrroloquinolines in high yields with excellent diastereo- and enantioselectivities. The presence of the thiourea functionality is crucial for the enantioselectivity of the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(26 citation statements)
references
References 106 publications
0
25
0
Order By: Relevance
“…Recently, we described that chiral phosphoric acids were efficient catalysts for the asymmetric IEDADA reaction of N‐arylimines ( 1 ) and enecarbamates ( 2 ) as dienophiles in a highly diastereo‐ and enantioselective manner (Scheme ) 10b,f,g. A study of the mechanism indicated that the simultaneous dual activation through hydrogen‐bonding interactions of the bifunctional phosphoric acid with both 1 and the NH donor group of 2 was critical for achieving high enantioselectivity 11–13.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we described that chiral phosphoric acids were efficient catalysts for the asymmetric IEDADA reaction of N‐arylimines ( 1 ) and enecarbamates ( 2 ) as dienophiles in a highly diastereo‐ and enantioselective manner (Scheme ) 10b,f,g. A study of the mechanism indicated that the simultaneous dual activation through hydrogen‐bonding interactions of the bifunctional phosphoric acid with both 1 and the NH donor group of 2 was critical for achieving high enantioselectivity 11–13.…”
Section: Methodsmentioning
confidence: 99%
“…We recently described the first examples of three‐component enantioselective Povarov reaction of aldehydes ( 2 ), anilines ( 3 ), and enecarbamates 4 (Scheme ) leading to the rapid and efficient generation of a range of 4‐amino‐1,2,3,4‐tetrahydroquinolines 1 6a,d,f. As a continuation of this research program, we wanted to extend this transformation to amino‐substituted aromatic substrates other than anilines.…”
Section: Methodsmentioning
confidence: 99%
“… The simultaneous creation of four new chemical bonds (three carbon–carbon bonds and one carbon–nitrogen bond) and five stereocenters including a spiro quaternary center in one‐pot. Less reactive styrene‐type substrates as the olefin component in the Povarov reaction (only three examples of an asymmetric catalytic protocol involving styrene derivatives as the dienophiles in Povarov reaction have been reported11c, 12m,j). The control of diastereo‐ and enantioselectivity of the products. …”
Section: Methodsmentioning
confidence: 99%
“…Less reactive styrene‐type substrates as the olefin component in the Povarov reaction (only three examples of an asymmetric catalytic protocol involving styrene derivatives as the dienophiles in Povarov reaction have been reported11c, 12m,j).…”
Section: Methodsmentioning
confidence: 99%